Algebraic Characterization of the Local Craig Interpolation Property - Gyenis, Zalán (Bulletin of the Section of Logic, 2018)
The sole purpose of this paper is to give an algebraic characterization, in terms of a superamalgamation property, of a local version of Craig interpolation theorem that has been introduced and studied in earlier papers. We continue ongoing research in abstract algebraic logic and use the framework developed by Andréka– Németi and Sain.